2016
DOI: 10.7324/japs.2016.60320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and chronic treatment of Cyclosporin A on liver and kidney functions in rats

Abstract: Cyclosporin A is a compound widely used as an immunosuppressive drug, particularly, in case of kidney transplantation to prevent rejection of transplanted organ. This study aimed to investigate the bad side effect of acute and chronic treatment with cyclosporin A on liver and kidneys by measuring liver enzymes and kidney function tests in serum. Male rats were used as experimental model in this study. The results of this study concluded that, chronic treatment with cycloosprin A leads to increase in serum urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Supplementation with zingerone decreased the activities of hepatic enzymes near those of the control values, which could be attributed to the ability of zingerone to prevent hepatic damage and dysfunction. Similar hepato-protective indings were observed by previous researchers (Swaroopa et al, 2012;Elsayed et al, 2016;Korolczuk et al, 2016). To con irm the hepatoprotective effect of zingerone, in our present study, the activity of AST & ALT was measured in liver tissues.…”
Section: Figure 1 Andsupporting
confidence: 87%
“…Supplementation with zingerone decreased the activities of hepatic enzymes near those of the control values, which could be attributed to the ability of zingerone to prevent hepatic damage and dysfunction. Similar hepato-protective indings were observed by previous researchers (Swaroopa et al, 2012;Elsayed et al, 2016;Korolczuk et al, 2016). To con irm the hepatoprotective effect of zingerone, in our present study, the activity of AST & ALT was measured in liver tissues.…”
Section: Figure 1 Andsupporting
confidence: 87%
“…[ 17,22 ] In this model, an initial time‐course study revealed that 25 mg/kg/day of CsA, when given for 28 days, produced a statistically significant increase in the levels of liver and kidney function markers (SGPT, SGOT, bilirubin, serum urea, BUN, and serum creatinine) as a result of hepatocyte and renal cell damage. [ 10,42–44 ] As a change in the levels of these markers beyond 21 days produced mortality, the study was designed till this time. The selection of this time point is in agreement with several other studies evaluating CsA induced organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…A steady decrease in hepatic protein levels with higher doses of ACR could be attributed to retarded protein synthesis, change in protein metabolism, or to the leakage of protein reserves from hepatocytes (Asha et al, 2008). Significant decrease of serum albumin and TSP were noticed after 2 weeks of treatment with Cys (Elsayed et al, 2016) that indicated hepatotoxicity (Kienhuis et al, 2013 Significant elevation in serum GSH and depression in peroxynitrite radical concentration after oral intubation of Salvia officinalis indicated its antioxidant capacity. Antioxidant and free radical scavenging activity of alcoholic and water extract of SO were studied in vivo (Oboh and Henle, 2009) and in vitro (Wielgus et al, 2011;Petrova et al, 2015) study as well as in SO nanoparticles (Wagdy and Faiza, 2013), Carnosic acid, carvacrol, thymol (Tenor et al, 2011) α-thujone and camphor (Pop et al, 2014) as well as rosmarinic acid and its dimer (salvianolic acid), showed a high antioxidant activity and is a very significant scavenger of free radicals (Hamidpour et al, 2014).…”
Section: Ne Usmentioning
confidence: 99%